Signal processing for cognitive radios - Jayaweera, Sudharman K., 1972- (Hoboken : John Wiley & Sons, Inc., 2015)
'This book covers power electronics, in depth, by presenting the basic principles and application details, and it can be used both as a textbook and reference book. Introduces the specific type of CR that has gained the most research attention in recent years: the CR for Dynamic Spectrum Access (DSA). Provides signal processing solutions to each task by relating the tasks to materials covered in Part II. Specialized chapters then discuss specific signal processing algorithms required for DSA and DSS cognitive radios'--
Includes references and index.
Keywords: Cognitive radio networks